(untitled) (Advancements in Homeopathic Research, 2025)
Polycystic ovarian syndrome is a complex endocrinopathy affecting reproductive age, causing obesity, menstrual irregularities, and hyperandrogenism. It is primarily caused by chronic persistent anovulation, which can result from various endocrinopathies. Homoeopathy offers an effective alternative for managing PCOS, with individualized remedies showing efficacy in this condition. This article will help the homoeopathic professionals to understand PCOS better from various aspects and select homeopathic remedies for the same.